Mechanistic insights into dehydrocoupling of amine boranes using dinuclear zirconocene complexes. Issue 12 (27th May 2021) - Lindenau, Kevin; Jannsen, Nora; Rippke, Mirko; Al Hamwi, Hanan; Selle, Carmen; Drexler, Hans-Joachim; Spannenberg, Anke; Sawall, Mathias; Neymeyr, Klaus; Heller, Detlef; Reiß, Fabian; Beweries, Torsten
Abstract : Catalytic dehydrocoupling of H3 B·NMe2 H using Cp2 Zr(Cl)(μ-Me3 SiC3 SiMe3 )Zr(Cl)Cp2 (1 )/MeLi was studied. Spectroscopic monitoring and stoichiometric experiments show the formation and interconversion of several catalytically active Zr species. Abstract : Catalytic dehydrocoupling of H3 B·NMe2 H using the in situ system Cp2 Zr(Cl)(μ-Me3 SiC3 SiMe3 )Zr(Cl)Cp2 (1 )/MeLi was studied as a model for previously reported dehydropolymerisation of H3 B·NMeH2 . NMR and UV-vis spectroscopic monitoring of the precatalyst activation sequence as well as a series of stoichiometric experiments showed that formation of a zirconocene dimethyl complex (2 ) is not relevant for activation of the precatalyst. Instead, deprotonation of H3 B·NMe2 H and reaction of thus formed Li[NMe2 BH3 ] is proposed to result in the formation of Zr amidoborane and hydride species. DFT analysis using such complexes as active species showed a pathway for formation of H2 and H2 BNMe2 . 1 H NMR spectroscopic monitoring and stoichiometric control experiments revealed the formation of unusual diamagnetic dinuclear complexes Cp2 Zr(C2 SiMe3 )(μ-R)ZrCp2 (R = CH2 SiMe3, 7 ; R = H, 9 ) formed by activation of the allenediide unit of the precatalyst 1 . Such species can be regarded as rare single-component catalysts for the dehydrocoupling of amine boranes.